Investigating How Psychological Safety Can Be Fostered in Agile Teams - Kaiser, André Luiz Nunes; Dutra, Eliezer; Santos, Gleison (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.9953, 2025)
Context: Psychological safety is defined as a shared belief that team members can take interpersonal risks at work without fear of reprisal. Technical, social, cultural, organizational, and personal factors can all influence psychological safety. Its absence in agile environments can negatively affect both software quality and project success. Problem: Although psychological safety has been studied in other areas, it is still underexplored in the agile context. Existing research examines only a few factors and the relationships between them. The lack of understanding of the factors that influence psychological safety limits the ability to take action to foster a psychologically safe workplace. Objective: Our goal is to summarize studies that investigate psychological safety in agile contexts, as well as to identify the factors that promote or affect psychological safety, in addition to the effects of its absence or presence. Method: We conducted a mapping study. Results: We found 21 studies that investigate psychological safety in the agile context. We identified that team performance, engagement, reflexivity, learning, software quality, and open communication, among other factors, emerge in organizational cultures that promote psychological safety, and that leadership behavior is a key element in sustaining a psychologically safe environment. Conclusion: We captured relevant factors for the study of psychological safety in agile contexts. The results can support future research on the topic and contribute to the development of new solutions to address it. Furthermore, the findings may serve as a basis for defining approaches to promote a psychologically safe environment and organizational culture.